Legal Analysis of Oral Indefinite-Term Employment Agreements (PKWTT) from the Perspective of Law No. 11 of 2020 on Job Creation - Hafidz Alkhairi; Fero Sanjaya; Herlita Eryke (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the legal aspects of oral indefinite-term employment agreements (PKWTT) within the framework of Law Number 11 of 2020 on Job Creation. The main issues examined include the legal validity of oral employment agreements, the differences in characteristics between fixed-term employment agreements (PKWT) and indefinite-term employment agreements (PKWTT), as well as the legal consequences arising from termination of employment (PHK), particularly unilateral termination by employers. This research employs a normative legal method using statutory and conceptual approaches, based on primary, secondary, and tertiary legal materials. The results show that oral employment agreements are legally valid within the context of PKWTT, as long as they fulfill the essential elements of a valid agreement and comply with applicable laws and regulations. However, to ensure legal certainty, employers are required to issue an appointment letter as formal evidence of the employment relationship. Furthermore, if a fixed-term employment agreement (PKWT) is not made in written form, it is legally converted into an indefinite-term employment agreement (PKWTT). In cases of termination of employment, workers under PKWTT status are entitled to severity pay, long-service awards, and compensation in accordance with prevailing regulations. Violations of these obligations may result in administrative and criminal sanctions as specified in the implementing regulations of the Job Creation Law. In conclusion, oral employment agreements in PKWTT are legally recognized; However, they require stronger administrative compliance and legal protection to safeguard workers' rights and ensure legal certainty in industrial relations. Keywords : Employment Agreement, PKWTT, Oral Agreement, Job Creation Law, Legal Certainty.